Investigations on the elasticity modulus of stone masonry. (April 2021) - Gonen, Semih; Soyoz, Serdar
Abstract: The modulus of elasticity of masonry is one of the main parameters used both in the assessment of the existing structures and in the design of new ones. The current practice in determining the modulus of elasticity of this type of structural material comprises significant uncertainties, which in turn affect the results of structural analysis considerably. This research investigates the elasticity modulus of the stone masonry wall using several experiments, numerical modeling, and empirical equations and highlights the sources of uncertainties in these methods. Knowing the advantages and drawbacks of the methods may help to reduce the uncertainties and choose the optimal experimental campaign for the associated physical circumstances of the encountered problem. The elasticity modulus found using the ambient vibration test is similar to the flat-jack and the vertical compression tests, and it represents the overall global behavior of the structure. Another objective of this research is to demonstrate the influence of the uncertainty in elasticity modulus estimation on the numerical analysis results. A straightforward modeling approach, commonly used by practitioners, is employed to show how the uncertainty in elasticity modulus of masonry propagates into the results of the analyses. The outcomes of this study call attention to the large variation of the elasticity modulus values and their implications in assessment and design.